Support leg action can contribute to maximal instep soccer kick performance: an intervention study. Issue 1 (2nd January 2017) - Augustus, Simon; Mundy, Peter; Smith, Neal
ABSTRACT: This investigation assessed whether a Technique Refinement Intervention designed to produce pronounced vertical hip displacement during the kicking stride could improve maximal instep kick performance. Nine skilled players (age 23.7 ± 3.8 years, height 1.82 ± 0.06 m, body mass 78.5 ± 6.1 kg, experience 14.7 ± 3.8 years; mean ± SD) performed 10 kicking trials prior to (NORM) and following the intervention (INT). Ground reaction force (1000 Hz) and three-dimensional motion analysis (250 Hz) data were used to calculate lower limb kinetic and kinematic variables. Paired t -tests and statistical parametric mapping examined differences between the two kicking techniques across the entire kicking motion. Peak ball velocities (26.3 ± 2.1 m · s −1 vs 25.1 ± 1.5 m · s −1 ) and vertical displacements of the kicking leg hip joint centre (0.041 ± 0.012 m vs 0.028 ± 0.011 m) were significantly larger ( P <  0.025) when performed following INT. Further, various significant changes in support and kicking leg dynamics contributed to a significantly faster kicking knee extension angular velocity through ball contact following INT (70–100% of total kicking motion, P  < 0.003). Maximal instep kick performance was enhanced following INT, and the mechanisms presented are indicative of greater passive power flow to the kicking limb during the kicking stride.